Ethos and Critical Discourse Analysis: From Power to Solidarity - Claudio Ramírez (Contextes)
Works within Critical Discourse Analysis tend to concentrate on the analysis of institutionally reproduced power by dominant groups in society. Furthermore, focusing on negative or exceptionally serious social or political events results in the transition of the object of inquiry from the use of power to the abuse of power or at least its socially negative consequences. Therefore, and despite the explicit aim of siding with non-dominant groups in society, Critical Discourse Analysis focuses solely on the discourse of dominant groups, paradoxically leaving the discourse on non-dominant groups underexposed. Borrowing from French and Argumentative Discourse Analysis, the article proposes the co-optation of the concept of ethos in order to alleviate this problem. Specifically, ‘solidarity in discourse’ is presented as a useful approach to ethos within a Critical Discourse Analysis framework. As an illustration of the concept of ‘solidarity’ in discourse, the article presents an analysis of two texts from a very different interdiscursive tradition: a military statement by the Zapatista guerrilla (EZLN) and a newspaper column by the late Venezuelan president Hugo Chávez.